Synergistic cooperative effect of CF3SO2Na and bis(2-butoxyethyl)ether towards selective oxygenation of sulfides with molecular oxygen under visible-light irradiation - Liu, Kai-Jian; Wang, Zheng; Lu, Ling-Hui; Chen, Jin-Yang; Zeng, Fei; Lin, Ying-Wu; Cao, Zhong; Yu, Xianyong; He, Wei-Min (Green chemistry : an international journal and green chemistry resource : GC, 2021)
A safe, practical and eco-friendly method for the switchable synthesis of sulfoxides and sulfones through visible-light-initiated oxygenation of sulfides at ambient temperature under transition-metal-, additives-free and minimal solvent conditions. The synergistic catalytic efforts between CF3SO2Na and 2-butoxyethyl ether represents the key promoting factor for the reaction.